1997
DOI: 10.1027/1015-5759.13.2.118
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Fear of Flying: Elaboration and Validation of a Videotape as an Analogous Situation of a Flight1

Abstract: The results are presented for the validation of a videotape as an analogous situation for a flight. The video includes the most significant elements of a flight by air: confirmation of the flight, packing, going to the airport, checking-in, going through the metal-detector, departure lounge, boarding the plane, demonstration of the personal safety drills, interiors and exteriors during the flight and landing. Two physiological measures are used for validation (heart rate and temperature) and a subjective measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The third instrument used for assessment was a video tape of a #ight. In a previous study (CapafoH ns et al, 1997b) the video tape has shown a di!erence between subjects with and without #ying phobia with an acceptable level of reliability. Furthermore, this instrument was able to detect changes produced by psychological treatment in phobic patients, taking into account psychophysiological and self-report information.…”
Section: Instrumentsmentioning
confidence: 88%
See 2 more Smart Citations
“…The third instrument used for assessment was a video tape of a #ight. In a previous study (CapafoH ns et al, 1997b) the video tape has shown a di!erence between subjects with and without #ying phobia with an acceptable level of reliability. Furthermore, this instrument was able to detect changes produced by psychological treatment in phobic patients, taking into account psychophysiological and self-report information.…”
Section: Instrumentsmentioning
confidence: 88%
“…The two groups together with the above-mentioned non-fear group were speci"cally analysed with respect to which subject was allocated to which group. The variables included in this discriminant analysis were the most representative of the whole set, selected by the analysis of the correlations resulting from the validation studies of the subjective scales of fear of #ying (Sosa et al, 1995) as well as the video tape exposure variables (CapafoH ns et al, 1997b). Table 2 shows means and standard deviations obtained from both fear groups before and after treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brandon and Kleinknecht (1982) used a videotaped simulated dental operation as a BAT to assess dental fear via self-report and physiological palmar sweating. Capafóns, Sosa, Herrero, and Viña (1997) carried out a study to validate an analogous observation with flight videos; they used subjective measurements, heart rate and temperature. This system identified people with or without a flying phobia and showed sensitivity to the treatment's effects.…”
Section: Creating a Computerized Instrument For The Assessment Of Blomentioning
confidence: 99%
“…Conversely both convergent and divergent validity is assessed with comparison to the Visible Analogue Flight Anxiety Scale (VAFAS), and the Fear Survey Schedule (FSS-III) (Wolpe & Lang, 1977) respectively. (Van Gerwen,Van Dyke & Diekstra, 1999) One study, (Capafóns, Sosa, Herrero, & Viña, 1997) notes the extra complexity of diagnosis, which in turn restricts research into this area. The authors assess the efficacy of using videotape to provide apparently provide "isolated stimulus", and concluding that that "viewing video evokes differences between phobics and non phobics at the subjective level."…”
Section: Treatmentmentioning
confidence: 99%